A study on the performance of various biofuel blends [electronic resource] - Soosai Sawarimuthu, 1985-; Fakulti Kejuruteraan Mekanikal (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2008